Analysis of the Utilization of Assessment Center Results in Civil Servant Career Development in the Regional Government of North Sulawesi Province - Matindas, Sebrina; Tampi, Jhony R. E.; Sampe, Stefanus (Journal of Public Representative and Society Provision, 2024)
Assessment center is a comprehensive method to assess the ability, competence and suitability of a person with a certain role or position, by measuring technical and non-technical competence. The North Sulawesi Provincial Government in supporting the bureaucratic reform process has the responsibility to implement employee development programs through the assessment center method before holding a position as a high-ranking official. This study was conducted to explain the utilization of assessment center results in career development (promotion, rotation/mutation, and competency development) of Civil Servants (PNS) in the North Sulawesi Provincial Government. Qualitative design was used in this study. The research findings that the utilization of assessment center results by the North Sulawesi Provincial Government in this case through BKD as the personnel management official has not been effective enough because there are still elements of subjectivity in the mutation/rotation of Officials/Employees. In terms of selection/filling of JPTP (Promotion), the North Sulawesi Provincial Government is committed to continuing to use the Assessment Center method even though in reality there are still elements of subjectivity when it is already in the selection committee. In addition, the results of interviews with informants indicate that the utilization of assessment center results has not been optimal due to various factors, including political intervention, lack of understanding of assessment centers, implementation of the merit system, organizational culture, talent management systems, and budget issues and availability of training, as well as regulations/legal umbrellas.